2014
DOI: 10.1007/s10916-014-0134-x
|View full text |Cite
|
Sign up to set email alerts
|

Automated Mapping of Clinical Terms into SNOMED-CT. An Application to Codify Procedures in Pathology

Abstract: Clinical terminologies are considered a key technology for capturing clinical data in a precise and standardized manner, which is critical to accurately exchange information among different applications, medical records and decision support systems. An important step to promote the real use of clinical terminologies, such as SNOMED-CT, is to facilitate the process of finding mappings between local terms of medical records and concepts of terminologies. In this paper, we propose a mapping tool to discover text-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The annotation results outperformed the approaches presented by Allones et al [5] and Shah et al [7] and compared very well to the ones presented by Topfer et al [6], who obtained slightly better results, and Elkin et al [4], whose results were slightly inferior to ours. This comparison of final metrics shows that the employed NLP pipeline and annotation algorithm deliver state-of-the-art results and provide an objective evaluation of the query results.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The annotation results outperformed the approaches presented by Allones et al [5] and Shah et al [7] and compared very well to the ones presented by Topfer et al [6], who obtained slightly better results, and Elkin et al [4], whose results were slightly inferior to ours. This comparison of final metrics shows that the employed NLP pipeline and annotation algorithm deliver state-of-the-art results and provide an objective evaluation of the query results.…”
Section: Discussionsupporting
confidence: 83%
“…Elkin et al analyzed mapping algorithms with the SNOMED (systematized nomenclature of medicine) ontology on chest X-ray reports with excellent results [4]. A similar task for pathology was recently presented by Allones et al but required further improvement [5]. In the German language, a 2015 paper presented by Toepfer et al showed very good results [6].…”
Section: Related Workmentioning
confidence: 99%
“…In conjunction with medical terminologies, a suitable report structure improves the addressability of particular contents for machines. There are different approaches on mapping the clinical terms occurring in free texts of documentations to medical terminologies, such as SNOMED CT, by using text mining methods (Stenzhorn et al, 2009;Spasic et al, 2005;Allones et al, 2014). Extracting machine-readable facts out of raw text facilitates the electronic exchange of the report information between information technology (IT) systems (Bouhaddou et al, 2008;White and Carolan-Rees, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Tujuan utama dari SNOMED CT adalah untuk mendukung rekaman klinis efektif data dengan tujuan meningkatkan perawatan pasien. Ini adalah koleksi terstruktur dari istilah medis yang digunakan secara internasional untuk merekam informasi klinis dan dikodekan dalam komputer secara processable (Allones et al 2014).…”
Section: Snomed Ct Snomed Ct (Sistematis Nomenklatur Of Clinicalunclassified